El desinterés por la música académica en los estudiantes del Instituto Superior de Música Público Daniel Alomía Robles, 2023 - Chaupis Espinoza, Cristian Antony (2025)
This This quantitative research, with a descriptive level, basic type, and nonexperimental design, aimed to determine the level of disinterest in academic music among students at the Daniel Alomía Robles Public Higher Institute of Music in 2023. The study involved a population of 91 enrolled students, from which a sample of 53 participants was drawn, ranging from the second to the tenth academic cycle. A questionnaire consisting of 19 questions, validated by three experts, was used as the data collection instrument. The questions addressed dimensions related to teacher disinterest, family involvement, emotional conditions, interaction, routine, and environment. The study concluded that the level of disinterest in academic music among students is predominantly moderate, as 66% of participants fell into this category, while 33% showed a low level of disinterest, and only 1% exhibited a high level. Upon analyzing the variables of gender, professional career, and instrumental specialization, no statistically significant differences were found, indicating that these factors do not significantly influence students' motivation toward academic music. This widespread moderate level of disinterest suggests the need to implement strategies and actions aimed at enhancing motivation and commitment to academic music within this student population.